Diplomazia pontificia e Comunità internazionale nel contesto del contributo della Santa Sede al bene dell’umanità (Stato, Chiese e pluralismo confessionale, 2022)
SOMMARIO: 1. La funzione e il ruolo della diplomazia pontificia nella Comunità internazionale - 2. Le dimensioni dell’attività diplomatica della Santa Sede dal pontificato di Giovanni Paolo II a quello di Francesco - 3. Il riconoscimento dei diritti umani nella diplomazia di Papa Francesco - 4. A servizio della pace nel mondo - 5. Libertà religiosa, cooperazione per il bene comune e promozione della persona umana - 6. Annotazioni conclusive.Diplomacy of the Holy See and the International Community In the context of the Holy See’s contribution to the good of mankindABSTRACT: The article takes into consideration the reasons and purposes for the presence of the ‘supreme governing body of the Catholic Church’ in the international Community. The author reflects on the relationship between the diplomatic activity of the Holy See and the delicate issues of peace and war. Therefore, attention is given to the methods of intervention put in place by Pope Francis with reference to the protection of fundamental human rights. In fact, from the pontificate of Paul VI, to those of John Paul II and Benedict XVI, to even the present pontificate of Francis, the juridical and geo-political questions concerning peace and terrorism, war and nuclear disarmament, the defense of religious freedom and the improvement of universal relations between states, the reform of international organizations and the promotion of human rights have strongly characterized the modus agendi of the two thousand year-old papal diplomacy. Faced with these questions, the Holy See seems to confirm both its own sui generis international juridical subjectivity and its own ‘positive neutrality’ by means of a significant work of mediation in offering universally shared solutions to protect the ontological, irrepressible dignity of the human person.